"Voting With Their Feet": Highly Skilled Emigrants From Southern Europe. (November 2014) - Triandafyllidou, Anna; Gropas, Ruby
In this article, the authors present new empirical data on highly skilled emigrants from two southern European countries, Italy and Greece, which have been particularly hit by the global financial and Eurozone crisis. The data have been generated by an e-survey conducted in late spring and summer 2013. Through analyzing the responses of Greek and Italian citizens who have chosen to emigrate, the authors present new insights on their educational backgrounds, the conditions that have motivated their decision to emigrate, and the way in which they have defined their migration project. It is argued that the decision to migrate is driven by a sense of severe relative deprivation as a result of the crisis and a deep frustration with the conditions in the home country. The crisis seems to have magnified the "push" factors that already existed in Italy and Greece and that now nurture this migration wave. At the same time, however, this migration is also framed within a more general perspective of a vision of life in which mobility and new experiences are valued positively and also seen as part of one's professional identity.